THE (POSITIVE) DESIGN ENVIRONMENT AS A PREREQUISITE OF DESIGN ORIENTATION (The South East European Journal of Economics and Business, 2021)
Design is a human-centered activity. Every design project starts with the analysis of user needs and preferences. This means that design orientation of a company should also be positively related to company’s business results. However, in most transitional countries of Central and Eastern Europe (CEECs), design environment is not supported, there is no clear national design policy, design implementation in companies varies, and there is no constant measurement of design impact. The main interest of this paper is to research the level of design implementation in Croatian companies related to the managerial approach and business results, because such research is usually undertaken in more developed countries. The study focuses on the perception of management. This quantitative research has been carried out using an Internet survey to examine managers and CEOs from Croatian companies in different industries. The results show positive relations between design environment and design orientation of a company and a significant impact of management.